Pengaruh Literasi Digital, Internal Locus of Control dan Dukungan Akademik Terhadap Niat Berwirausaha Mahasiswa di Kabupaten Banyumas - Yordan Hermawan Apidana (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2022)
One way to overcome unemployment and improve the Indonesian economy is to increase the entrepreneurial intention of the community and the younger generation, especially students through entrepreneurship programs which are expected to be able to improve the Indonesian economy and give birth to many entrepreneurs who provide many jobs so that people can choose jobs that match their skills. This research is a quantitative research and the respondents in this research are 326. In this study the sample was taken by means of non-probability sampling, namely accidental sampling technique. Based on data analysis, it is known that: (1) digital literacy has no effect on students' entrepreneurial intentions, (2) internal locus of control affects students' entrepreneurial intentions, (3) academic support affects students' entrepreneurial intentions.